2022
DOI: 10.3390/ma15082955
|View full text |Cite
|
Sign up to set email alerts
|

Wettability and Surface Roughness Analysis of Laser Surface Texturing of AISI 430 Stainless Steel

Abstract: Due to its wide applicability in industry, devising microstructures on the surface of materials can be easily implemented and automated in technological processes. Laser Surface Texturing (LST) is applied to modify the chemical composition, morphology, and roughness of surfaces (wettability), cleaning (remove contaminants), reducing internal stresses of metals (hardening, tempering), surface energy (polymers, metals), increasing the adhesion (hybrid joining, bioengineering) and decreasing the growth of pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 74 publications
2
25
0
Order By: Relevance
“…Two hundred shots were applied to each of the samples, with a power density of ~2 × 10 7 W/cm 2 . The results obtained and the related conclusion that the laser fluence is directly influenced by ablation, is consistent with the results obtained in relation with this research and presented in a previous paper of Moldovan E. et al [24].…”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations
“…Two hundred shots were applied to each of the samples, with a power density of ~2 × 10 7 W/cm 2 . The results obtained and the related conclusion that the laser fluence is directly influenced by ablation, is consistent with the results obtained in relation with this research and presented in a previous paper of Moldovan E. et al [24].…”
Section: Introductionsupporting
confidence: 93%
“…For example, for polymers it is between 0.1 to 1 J/cm 2 , while for inorganic insulators it is between 0.5 and 2.0 J/cm 2 [2]. Related to the present study, Moldovan E. et al [24] showed a decrease in fluence values from 8.49 J/cm 2 to 2.55 J/cm 2 , in the frequency range of 30-100 kHz. The materials have a different behavior under the action of the laser.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…The friction characteristics of the surface can be effectively improved by machining the texture with regular geometric dimensions and an orderly arrangement on the part surface. Surface modification has been widely used in many fields; for example, in the field of material surface friction reduction [2][3][4] and friction pair surface wear resistance [5,6], on some special occasions where surface friction needs to be increased [7], in environments where the system needs to reduce vibration [8][9][10], in the special field of resistance to adhesion [11], in the special environment of anti-creep [12], with long-term low-temperature equipment [13], and when the equipment needs to increase the bearing capacity [14], in the field of maintaining wettability [15], as well as areas with functional hydrophobicity requirements [16] and scenarios with increased adhesion [17]. It has shown good application prospects and become an effective way to achieve the high efficiency, miniaturization and high reliability of mechanical equipment [18].…”
Section: Introductionmentioning
confidence: 99%